ЛІТЕРАТУРА Й АНЕКДОТ: ДЕЯКІ ЄВРЕЙСЬКІ ОБРАЗИ У ТВОРАХ ІВАНА ФРАНКА (World Science, 2020)
In this article, we will try to analyze the integration of Jewish images and motives, peculiar of folk humorous works, throughout the period from the 17th to the 19th century. Therefore, arises another problem, namely how and from which perspective the Jewish ethnotype and its relationships with the Ukrainians are presented in literary works of the specified period and which criteria should we utilize for the analysis of such works, along with folk anecdotes. Finally, our third assignment is to determine the interrelation between folklore and literature in terms of its expression and levels on the basis of Ivan Franko’s works.